Optimization of Controlled-Release Microspheres Containing Vitexin and Isovitexin Through Experimental Design and Evaluation of Their Hypoglycemic Effects - Nhu Huynh Mai; Hoang-Han Do; Phi Hoang Yen Tran; Cong-Phi Nguyen; Van-Ha Nguyen; Ngoc Phuc Nguyen Nguyen; Kien-Duc Ngo; Duc-Tuan Nguyen; Minh-Quan Le (Pharmaceutics, 2025)
Background/Objectives: Vitexin and isovitexin are bioactive flavonoids with promising pharmacological effects; however, they have poor bioavailability. Microencapsulation with biodegradable polymers is a promising strategy for improving their stability, bioavailability, and biocompatibility. This study aimed to optimize the formulation parameters to obtain microspheres with desired properties in terms of size, loading ratio, and vitexin–isovitexin release. Methods: Microspheres were prepared using alginate as the core matrix and a chitosan outer layer. A Design of Experiment approach using response surface methodology was employed. The hypoglycemic effects of the obtained microspheres were evaluated. Results: The formulation using 1.17% low-viscosity alginate, 7.60% calcium chloride, 5.78% Tween 80, and 5.00% Span 80 resulted in microspheres with optimal mean size (10.78 µm), high loading ratio (22.45%) and encapsulation efficiency (68.92%). The in vitro release of vitexin–isovitexin from microspheres was completed within 24 h in controlled manner. The microspheres were found to be non-toxic in vivo and exhibited hypoglycemic effects after 21 days at doses equivalent to 30 and 60 mg/kg of vitexin–isovitexin. The potential mechanisms might involve increasing the size of Islets of Langerhans and improving pancreatic β-cell function and insulin resistance, as observed in alloxan-induced diabetic mice. Conclusions: This work successfully developed alginate–chitosan-based microspheres for the controlled release of vitexin–isovitexin while maintaining their bioactivities.